THE DIVERSITY OF STONY CORAL AND THE TENDENCY TO BLEACH BASED ON LIFEFORM IN THE TENGAH PATCH-REEF OF KARIMUNJAWA ISLANDS - Aradea Bujana Kusuma; Erwin Riyanto Ardli; Romanus Edy Prabowo (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Coral reefs, the habitat of tens of thousands of marine species, are an ecosystem with the highest biodiversity. Several threats, however, have impaired coral reefs. One having a potentially catastrophic effect is the increasing temperature of the ocean that leads to a coral bleaching event. This study aimed to determine the diversity of stony coral based on their lifeform, to assess the condition of reefs by measuring percent cover of live coral, and to determine the bleaching occurrence based on the stony coral lifeform in the Tengah patch-reef of Karimunjawa National (Marine) Park. The research was a visual survey with line intercept transects (LIT) used to collect data. The data were presented as percent cover of living coral and their lifeforms. The result showed the diversity of coral in the Tengah patch-reef was very high as indicated by the presence of all coral lifeforms in the study site. The most diverse lifeform was found at 10 m depth with 13 lifeforms, while the lowest lifeform was found at 3 m depth with ten lifeforms. The most extensive live coral cover was found at 3 m depth estimated around 73.71%, and the the lowest coverage was found at 10 m depth, no more than 50.42%. The bleaching event was found in Acropora branching and Acropora digitate at the 3 m depth